2009
DOI: 10.1167/iovs.08-2591
|View full text |Cite
|
Sign up to set email alerts
|

Role of PI3K/Akt and MEK/ERK in Mediating Hypoxia-Induced Expression of HIF-1α and VEGF in Laser-Induced Rat Choroidal Neovascularization

Abstract: The PI3K/Akt pathway was required for hypoxia-induced expression of HIF-1alpha and VEGF, whereas the MEK/ERK pathway was required only for VEGF in laser-induced rat CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 33 publications
10
107
1
1
Order By: Relevance
“…VEGF is one of the most well-characterized angiogenic factors in CNV and is regulated by HIF-1 (17). Previous studies have demonstrated that hypoxia induces VEGF production in several cell types (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is one of the most well-characterized angiogenic factors in CNV and is regulated by HIF-1 (17). Previous studies have demonstrated that hypoxia induces VEGF production in several cell types (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway is activated during ischemia and angiogenesis (Yang et al, 2009). It regulates a variety of cellular processes and plays a critical role in controlling the balance between cell survival and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hypoxia may have a central role in the development of submacular wound healing, which in turn leads to the production of HIF-1, itself the key trigger for VEGF production and the subsequent development of the neovascular component of this submacular tissue repair. 52 HIF-1 regulates many angiogenic factors such as VEGF, VEGFR-1, erythropoietin, inductible nitric oxide synthase, endothelin-1 and plateletderived growth factor-B, which have important and diverse roles in different stages of angiogenesis. 28,53 Earlier studies have indicated that disruption of the binding between HIF-1 and proangiogenic promoters may selectively diminish the activation of the HIF-1-driven target genes.…”
Section: Discussionmentioning
confidence: 99%
“…As notable expression of HIF-1a was detectable since 1 day after laser photocoagulation and peaked at 3 day in pervious research, 52 the specimens at 3 day after laser photocoagulation were chosen for semiquantitative analysis of HIF-1a protein expression. Cryostat sections were dried in the air and rehydrated with PBS, blocked for 2 h in PBS containing 5% bovine serum albumin, 5% normal goat serum, and 1% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%